PEMANFAATAN PUPUK KOMPOS JAGUNG MANIS DALAM MENINGKATKAN PRODUKSI TANAMAN JAGUNG (Zea mays L) PADA TANAH ULTISOL - A Haitami; Wahyudi Wahyudi (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2019)
ABSTRACT The aim of this research was to study influence utilization of composted corn straw fertilizer in improving the production of plant corn (Zea mays L.) on an ultisol soil. The research was conducted at Koto kari Kuantan Singingi of Riau, from Mei to July 2017. It used a Randomized Bolock Design Consisting of 5 levels of treatment and 3 groups so that there are 15 experimental units. The treatment given is: A = No Treatment (control), B = Compost of Corn Straw 10 tons / ha + 100% inorganic fertilizer, C = Corn straw Compost 20 tons / ha + 100% inorganic fertilizer, D = Corn straw Compost 30 tons / Ha + 100% inorganic fertilizer, E = 100% Inorganic Fertilizer. The observed parameters were Plant height (cm), Age of female flower (HST), Harvest Age (HST), Heavy corn weight (gram), and Weight of corn without gram (gram). Data of observation result of each treatment were analyzed statistically and performed by Brightness Honest test (BNJ) at 5% level. Composting of corn straw compost has significant effect on all parameters of observation, where the best treatment is the application of 30 tons / ha of 100 ml of corn straw compost / 100 inorganic fertilizer.